Dictionary Skills Training in the Primary School ELT Classroom: A Taiwan Case Study From a Textbook Perspective. - Law, Wai on (Lexicography, 2026)
This study is an attempt to bridge a research gap in pedagogical lexicography in primary education. As a descriptive case study, it uses the documentation method to explore English dictionary skills training (DST) in primary school education in Taiwan. First, an examination of the Curriculum Guidelines of the Ministry of Education revealed its scant inclusion of dictionary skills training. Then, two students' attributes or learning performance listed in the Guidelines were identified and used as performance indicators to measure if the three shortlisted primary school English textbook series in Taiwan have adhered to the official curriculum in designing DST. Also, a questionnaire was sent to editors of the three selected textbook series to elicit their views on DST for primary school students. To better understand how DST is taught in the primary school classroom, a similar questionnaire was sent to primary school English teachers to solicit their responses on DST. Findings of the study indicate that not all series follow the government guidelines closely, despite their claims in the textbooks' external matter. Data from the two editors who responded to the questionnaire cited English teaching methodology or incompatible learning aims as the reason to exclude DST in textbook design. No response was received from English language teachers. Recommendations concerning the national curriculum and suggestions for textbooks and teachers are made to improve DST at the primary school level. The contribution of the present study is that it offers findings of a case study on DST at the primary school level, a hitherto neglected area in pedagogical lexicography.